O papel das representações sociais na relação entre a percepção de eficácia do movimento negro e o preconceito racial - Leite, Eldo Lima (2019)
This thesis aimed to test the hypothesis that the relationship between Black Movement Efficacy Perception and Racial Prejudice is explained by the Social Representations of this movement. To achieve this goal, this thesis was composed of two articles. The first article aimed to verify the brazilians’ social representations about the Black Movement and to verify if in these representations there are contents that allow to affirm if this Movement has been perceived like effective form. Participated of this study 173 university students from the State of Paraíba, with a mean age of 22.16; SD = 5.4; 32.9% were males and 67.1% were females. The average income of participants was R$ 5450,80; SD = 5368.26. Regarding to color, 40% were white and 60% brown. Data were analyzed using the technique of content analysis and lexical analysis. The results showed that the Black Movement is represented by ideas regarding the nature of the conflicts experienced by the black population, evocations regarding slavery; as well as an active vision of coping with such social problems. The lexical analysis of the justification of the efficacy of the Movement demonstrated that the Black Movement is perceived from different social visions: Social abandonment, Social Indifference; Positive Vision and Negative Vision of Movement. Finally, the results of the achievements demonstrated that the fight against discrimination, quota policies, the abolition of slavery, the valorization of black identity are the main achievements already achieved by the Movement. Article 2 sought to test the hypothesis that the relationship between Black Movement Efficacy Perception and racial prejudice is explained by the social representations of this movement. These representations were derived from Article 1 of this thesis. First, a pilot study was carried out with 164 university students from State of Paraíba, with a mean age of 22.20; SD = 5.46; with 31.1% male and 68.9% female. The average income of the participants was R $ 5298,46; SD = R $ 5172.41. Regarding color 41.1% were white, 47.9% brown and 11% black. It was verified that the Black Movement Efficacy Perception, operationalized in terms of achievements, was related to variables of political participation, as foreseen in the literature. Then a second study was performed to test the hypothesis of this thesis. Participated of this study 171 individuals from the general population, with a mean age of 31.48; SD = 9.52; 35.1% of males and 64.9% of females. The average income of participants was R$ 3882.26; SD = R $ 3497. Regarding to color, 42.7% were white, 42.1% brown and 15.2% black. The results showed that Movement Efficiency Perception is significantly related to racial prejudice measures. All regression models derived from the relationship between Movement Efficacy Perception and racial prejudice measures were mediated by the social representations of the Movement, confirming the main hypothesis of this thesis. Finally, a third study was carried out to test the hypothesis that the mediating effect of social representations in the model is independent of the effect of the variables perceptions of real and symbolic threat. The sample consisted of 193 university students, with a mean age of 20.93; SD = 4.24, being 45.6% male and 54.4% female. Regarding color, 40.4% was white, 51.3% brown and 8.3% black. The results demonstrated that the representations of the Movement have an effect independent of the perceptions of threat. These results suggest that the social representations of the Black Movement are one of the main factors that should be used as a political instrument in the struggle of the Black Movement against Racial Prejudice.